THE FORMING OF SCENARIOS OF STRATEGIC MANAEGMENT - B. V. Artamonov (Научный вестник МГТУ ГА, 2016)
The article considers the issues referring to the analysis and prognosis of enterprises activities in the conditions of high turbulent market as nellas to the developinent of scenarios oftheir long-term developinent.